Modification of Vanadium Phosphate Catalysts Synthesized Via the Hydrothermal Method - Theam, Kok Leong (2008)
Vanadium phosphorus oxide (VPO) catalysts synthesized via hydrothermal method were investigated. Some different dopants, Cr, Ni, Fe and Mn were used in the preparation of catalyst precursors, VOHPO4⋅0.5H2O. Besides, the mechanochemical treatments were introduced to the catalyst precursor with different milling durations in cyclohexane. All these modified precursors were subsequently transformed under reaction condition to give the active phase of VPO catalysts, (VO)2P2O7. Several techniques were used to characterize the physico-chemical properties of the catalysts such as XRD, BET, H2-TPR, redox titration, Laser Raman Spectroscopy and ICP-AES. The catalytic performance of the catalysts for selective oxidation of n-butane to maleic anhydride has been carried out by using a fixed bed microreactor (673 K, GHSV=2400 h-1). The results showed that the addition of dopants into the VPO catalysts had increased the surface area of the catalysts. Introduction of dopants had also induced the formation of V5+ phases as shown in XRD and Raman Spectra. However, a further extraction step with water at reflux temperature gave only catalysts with (VO)2P2O7. Interestingly, the doped samples showed a higher total amount of O2 removed from the oxygen lattice of the catalyst. The doping and water reflux treatment had affected the morphologies of the catalysts. The introduction of mechanochemical treatment produced materials with a mixture of V4+ and V5+ phases. SEM micrographs showed that the morphology of catalysts which milled in cyclohexane was in smaller platelet compared to the unmilled material. A significant high surface area was obtained for catalysts milled for 30 minutes (40 m2g-1) and 60 minutes (36 m2g-1). However, a longer milling duration drastically lowered the surface area due to the agglomeration of the particles as observed in the SEM micrographs. H2 -TPR revealed two type of oxygen species removed for all the catalysts associated with V5+ and V4+. The amount of active oxygen species removed associated with V4+ was significantly increased for 30 min mechano-treated. An increase of the oxygen species associated with V4+ phase which was correlated to the catalytic activity and a higher amount of oxygen species released associated to V5+ phase also contributed to the activity of the catalysts.